A Major North - West Dyke Swarm Zone in North Queensland - Chappell BW (The Australasian Institute of Mining and Metallurgy, 1987)
A zone of northwest trending dykes extends for over 600 km in the hinterland from Cairns to Mackay. In sate regions the zone is up to 120 km wide. Figure 1 shows their approximate extent, compiled from published regional maps and from specific studies in more limited areas : Palm Islands, Cardwell Ranges, Jourama Falls, Townsville area and Burdekin Delta. The context of the dyke swarm is the Tasman Orogenic Zone, the region of Eastern Australia conprised of Palaeozoic metamorphic, sedimentary, volcanic and plutonic rocks which has experienced a complex history and evolution. In the Whitsunday region, the Tam-an Zone also involves Cretaceous volcanism and plutonism. Geological relationships indicated a wide span of ages for the intrusions in the dyke, swarm zone. They intrude a range of volcanic and sedimentary rocks, and in some areas plutonic rocks. Older dykes, apparently part of the same regional swarm are intruded by sate of the granites.